Visual Ethnography of Education - Marglois, Eric (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is a small seminar and each participant is expected to make a major contribution to its intellectual life. Each person will: 1) do all the reading, become familiar with the texts and take responsibility for helping us understand them, 2) help us apply that knowledge by producing one or more visual ethnographies. You may choose to work alone on a project ori n a group. The final project will need to be approved by the instructor but otherwise you are free to work on any project that fits the broad description of visual ethnography provided above.